Bone marrow stem cell therapy for stroke - Jin, Kunlin; Ji, Xunming; Zhuge, Qichuan (Springer, 2017)
This book covers recent advances in all aspects of bone marrow-derived stem cells (BMSCs) for stroke treatment, while also providing comprehensive information on human clinical trials and animal models of stroke. In addition, it reviews the optimal conditions of transplantation for stroke therapy and potential mechanisms underlying transplanted cell-mediated functional recovery after stroke. As the first book to focus on BMSC therapy for stroke, it also discusses in depth the unique challenges of BMSCs-based therapy in this context.
Keywords: Mesenchymal stem cells.; Cerebrovascular disease -- Treatment.; elektronické knihy; electronic books